2016
DOI: 10.1039/c6dt00321d
|View full text |Cite
|
Sign up to set email alerts
|

Ca(ii) and Ce(iii) homogeneous alginate hydrogels from the parent alginic acid precursor: a structural study

Abstract: Alginate hydrogels are suitable for the encapsulation of biomolecules and microorganisms for the building of bioactive materials. Several alternatives to the conventional alginate formulation are being studied for a broad range of biotechnological applications; among them the crosslinking of alginate by lanthanide cations, Ln(iii), envisages expanded biomedical applications. The performance of these functional materials is highly related to the microstructure of the alginate matrix, which in turn is affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
1
26
0
1
Order By: Relevance
“…Moreover, the Ca(II)-alginate structure can be obtained by cation exchange from a parent H-alginate hydrogel (Sonego, Santagapita, Perullini, & Jobbágy, 2016), 4 indicating a higher affinity of alginate polymer for Ca 2+ . It has been demonstrated that the combined use of alginate with sugars and/or other biopolymers such as arabic and guar gums allows to improve the stability of enzymes within the hydrogel (Traffano-Schiffo et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Ca(II)-alginate structure can be obtained by cation exchange from a parent H-alginate hydrogel (Sonego, Santagapita, Perullini, & Jobbágy, 2016), 4 indicating a higher affinity of alginate polymer for Ca 2+ . It has been demonstrated that the combined use of alginate with sugars and/or other biopolymers such as arabic and guar gums allows to improve the stability of enzymes within the hydrogel (Traffano-Schiffo et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…All the alginate-Ca(II) beads analyzed showed isotropic scattering and were modeled as a fractal system composed of rod-like structures, although the rigorous interpretation of experimental results as indicating "fractality" requires many orders of magnitude of power-law scaling. 20 Three parameters were analyzed: i) α1, the fractal dimension at distances higher than R, which describes the multiplicity of the junction zone, at q < 0.28; ii) α2, the fractal dimension at distances lower than R, at q > 0.55,…”
Section: Microstructure Characterizationmentioning
confidence: 99%
“…In macroscopic systems, and likely here in the microfluidic system, external gelation creates a gradient of polymer and crosslinking concentration and makes control over total calcium content and gelation rates difficult to achieve. 40,57,58 In comparison, internal gelation allows for a consistent calcium to carboxyl molar ratio to be set. 40 The resulting microgels exhibited larger diameters, diminished storage moduli, and higher degrees of swelling in comparison to external gelation.…”
Section: Discussionmentioning
confidence: 99%